Illness Representations of Hypertension among Nepali Patients at a Tertiary Care Hospital Clinic: An exploratory survey - Sah, Ram Kishor; Straus, Andrea; Shrestha, Deepak Sundar; Khanal, Hari Har; Paudel, Bishnu Dutta; Love, Richard R. (Journal of Nepal Health Research Council, 2021)
Background: The prevalence of stage 2 hypertension approaches one-third in adult Nepalis and despite inexpensive effective treatment, long-term compliance is poor. World-wide, a major impediment is the incongruity between hypertension and patients’ symptom-based illness representations. The Common-Sense Model of Self-regulation was used to investigate Nepali illness representations through open-ended interviews of patients with hypertension. Methods: In a tertiary hospital setting, 50 self-identified hypertensive patients were interviewed about their representations of health, hypertension, and hypertensive treatment. Responses were analyzed with a modified Interpretative Phenomenological Analysis. Results: An Ayurvedic-influenced health model appeared in illness identity and coping responses. Hypertension was identified as a serious disease having observable, wide-ranging symptoms with chronic and intermittent timelines. Concerns included side-effects and barriers to treatment. Conclusions: Further confirmation and investigation of Nepali common-sense hypertension models in a sample size sufficient for factor analysis is warranted for effective adherence interventions. Keywords: Common-sense model; hypertension adherence; illness representations; Nepal